Diagnostic approaches to bile leaks from the duct of Luschka - Sahil, Sheikh J.; Elina, Sor (International Surgery Journal, 2025)
Bile leaks from the duct of Luschka, also known as subvesical bile ducts, are a rare but clinically significant complications of cholecystectomy, being an etiology of Strasberg type A bile duct injury. Leaks pose a diagnostic challenge due to anatomic variation and non-specificity of presentation. The article provides a detailed examination of diagnostic methods which begin with clinical assessment and continue through laboratory testing and imaging techniques including ultrasound, computed tomography (CT), magnetic resonance cholangiopancreatography (MRCP), hepatobiliary iminodiacetic acid (HIDA) scan, endoscopic retrograde cholangiopancreatography (ERCP), intraoperative cholangiography, contrast-enhanced ultrasound (CEUS), and other emerging imaging technologies. The research presents diagnostic accuracy metrics and develops a diagnostic algorithm which enables medical professionals to reach fast. Precise diagnoses while ensuring patient safety.